Consumer Perceptions of Lawn Fertilizer Brands - Hayk Khachatryan; Alicia Rihn; Michael D. Dukes (EDIS)
Widespread urbanization in the United States has increased the number of lawns. A healthy lawn provides many benefits, including urban heat dissipation, water quality protection, erosion control, carbon sequestration, community safety, aesthetics, and property value growth. Many homeowners maintain their healthy lawns by applying fertilizers throughout the growing season, but excess fertilizer runoff and leaching have received much attention recently because of waterway pollution and algae blooms, leading many states to place restrictions on what chemicals can be used in lawn fertilizers.